Determinants of the performance of AVEC in the Nyiragongo territory, the city of Goma, and the town of Sake - OLENGA TSUBA Charles (IJRDO- Journal of Educational Research, 2024)
This article aims to find out if the Vilageoises Savings and Loan Associations (VSLAs) operating in these three entities are performing well and what are the factors that explain this performance. The study uses the econometric method with multiple linear regression. By taking into account two variables, namely savings per member and return on savings (ROS), the article offers various results. There is a significant difference in the level of profitability on savings depending on whether VSLAs operate in the city of Goma, in the city of Sake and in the territory of Nyiragongo. The return on savings is on average 0.26% higher for VSLAs based in the territory of Nyiragongo than for VSLAs based in the city of Goma. The age of the VSLA has a negative effect on the return on savings. It also appears that male-led VSLAs are less profitable than those led by women. Profitability on savings also increases with the percentage of members in debt at the end of the cycle. In addition, VSLAs that practice accounting achieve an average return on savings of 1.55% more than those that do not practice accounting. Regarding savings per member, the results mention that of all the explanatory variables taken into account, eight variables are statistically significant at the 1%, 5% or 10% threshold. These are the variables savings line, credit line, middle, active members, gender of the manager, total subscription, financial education, number of members in debt at the end of the cycle, as well as bookkeeping by the VSLA.